Tri-metallic Co-Ni-Cu based metal organic framework nanostructures for the detection of an anticancer drug nilutamide - Akhter, Shamima; Nurul Khairiyyah, Mohd Zain; Md., Shalauddin; Singh, Vivek Kumar; Izan Izwan, Misnon; Sharma, Rajendra Kumar; Das, Santanu; Wan Jeffrey, Basirun; Mohd. Rafie, Johan; Rajan, Jose (Elsevier, 2021)
This work reports a biosensor based on tri-metallic organic framework (MOF) for the determination of an anticancer therapeutic agent, nilutamide (NLM). The tri-metallic Co-Ni-Cu-MOF and the single metal MOFs Co-MOF, Ni-MOF and Cu-MOF were grown onto nickel foam (NF) substrate by a solvothermal method. The crystal, chemical structure, morphology and surface area of the MOFs were studied by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) transmission electron microscopy (TEM) and Brunauer-Emmett-Teller (BET) analysis. The electrochemical sensing of NLM by the Co-Ni-Cu-MOF/NF and the single metal MOFs grown onto NF were studied by cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS). The CV of the Co-Ni-Cu-MOF/NF shows a redox couple between -0.4 V and 0.3 V in phosphate buffer solution at pH 7.0. The Co-Ni-Cu-MOF/NF sensor shows a strong electrocatalytic activity towards the redox reaction of NLM with a broad concentration range from 0.5–70 μM and 70–900 μM with high sensitivity of 10.712 μA μM−1 cm-2 and a low limit of detection of 0.48 ± 0.02 nM. These results confirm that the tri-metallic MOF possesses high selectivity and sensitivity for the determination of NLM from human serum specimen and pharmaceutical tablet dosage forms.